Sizing of hybrid photovoltaic and wind system for Block A residential hostel - Salad, Yusuf Hassan (2021)
This Project discussed the sizing Process of stand-alone Photovoltaic (PV) and wind system to supply the required load for Residential hostel located in Parit Raja, Malaysia. Energy from renewable sources is clean, eco-friendly, efficient, and reliable. Solar and wind are gaining much importance in the present world. It is important to establish renewable energy in an isolated area where the availability of fuel is costly for grid expansion. The procedure of this research was the measuring and collection of the basic meteorological data of solar radiation and wind speed for Parit Raja. The project aims to size the stand-alone system was by using manual calculation and HOMER Pro software. However, solar and wind energy are known as dependable and widely available renewable energy sources in Malaysia, but the intermittent energy sources will cause the power generator to produce a fluctuating output when it's overcast or night-time, one can't power our system utilizing a stand-alone PV system since there is no solar radiation. Similarly, the varying wind speed will affect the amount of energy generated by a standalone wind turbine system. The simulation results showed that a hybrid system consists of 58kW photovoltaic modules with one wind turbine (20 kW), 15kW inverter, and 1 kWh battery storage (48batteries, 200 Ah, and 12 V) produced electricity for a residential hostel and cost of electricity of RM0.703 per Kwh. finally, the PV system ended up being the most cost-effective solution, while also being the most efficient in terms of energy usage.